Antimicrobial activity of essential oils of plants belonging to Lamiaceae juss. family - Shanayda, M; Pokryshko, O (Annals of Mechnikov's Institute, 2020)
Introduction. One of the important sources of therapeutic and prophylactic agents of modern medicinesare essential oils of medicinal plants. Essential oils are the main group of biologically active substances of a number of plants belonging to Lamiaceae Juss. Family. Antibacterial activity of medicinal plants belonging to Lamiaceae Family many scientists associated with containing of essential oils. In this regard, considerable interest presents the comparative analysis of the antimicrobial properties of essential oils of Lamiaceae Family representatives. Material and methods.The antimicrobial activity of essential oils of investigated plants was studied with using in vitro condition. The essential oils derived from the aerial parts of cultivated plants of Ocimum, Hyssopus, Dracocephalum, Lophanthus, Monarda and Satureja genus harvested during flowering period (in terms of Ternopil region). The antimicrobial activity of essential oils studied plants was studied by serial dilution method and disk diffusion assay.It has been applied on standard microorganism test strains: Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 9027 and Candida albicans ATCC 885-653. Results and discussion. It was conducted a comparative study of the influence of some essential oils of cultivated plants belonging to Lamiaceae familyon microorganisms in conditions in vitro. It was found that essential oils of the studied plants were most effective in the maximum concentration (1:10). Gram-positive cocci S. aureus and yeast C. albicans were the most sensitive to influence of investigated essential oils. It was analyzed the relationship of the biological activity with the component composition of essential oils of plants. Essential oils of L. anisatus, M. fistulosa and S. hortensis characterized by the dominance of aromatic compounds and had shown stronger antimicrobial activity than essential oils of other species.Therefore, essential oils of these speciesare very promising source of antibacterial and antifungal drugs, especially in the treatment and prevention of skindiseases, upper respiratory tract inflammations and vaginitis.Conclusion. Obtained results indicate promising further study of antibacterial properties of essential oils of plants species L. anisatus, M. fistulosa and S. hortensis (Lamiaceae family). It was discovered that Gram-positive cocci, including S. aureus, and yeast Candida were the most sensitive to these oils. Along with the prospect of creating antimicrobial drugs which include essential oils of studied plants these oils can be recommended as active ingredients of preservatives in the composition of cosmetic products or dietary supplements also.